Wara' Upaya Menjaga Agama dan Kehormatan dari Syubhat: Studi Takhrij dan Syarah Hadis - Hana Mariatul Qibtiyah; Fitriani Fitriani (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about wara` and shubhat. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about wara` efforts to maintain religion and honor from shubhat in Bukhari's narration No. 50. The results and discussion of this research show that the status of the hadith hasan li ghairihi quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Bukhari No. 50 is relevant to be used as motivation and reminder in every case in daily life.